O olhar de uma roteirista: a construção do cinema escrito de Suso Cecchi D'Amico - Ana Luiza Cavalcanti Fatorelli Carneiro (2023)
This thesis investigates the construction process of the "written cinema" of the Italian screenwriter Suso Cecchi D'Amico, from the scripts and documents produced for the making of the films. During her 60-year career, Suso has worked with great directors in more than 100 films. Stories, synopses, step-outlines, character studies, sketches, reports and letters sent to the group are the first forms of films. Since the screenwriter almost always worked collectively, carrying out the search and analysis of these documents, often ephemeral and practically unpublished, was the possibility of affirming the author's real contribution in the films in which she collaborated, demonstrating her relevance to the history of Italian cinema. The idea was to find in the genesis of the film construction process, the marks of a "screenwriter film director".